One day I shall astonish the world - Stibbe, Nina (Little, Brown and Company, 2022)
"Susan and Norma have been best friends for years, at first thrust together by force of circumstance (a job at a haberdashery shop in 1990s Leicestershire) and then by force of character (neither being particularly inclined to make friends with anyone else). But now, thirty years later, faced with a husband seeking immortality and Norma out of reach on a wave of professional glory, Susan begins to wonder whether she has made the right choices about life, love, work, and, most importantly, friendship"--